“The Writer at the Far Margin” - Paula Martín Salván (European Journal of American Studies)
This article analyzes Don DeLillo’s narrative in terms of the artistic ethics built into it in connection to the ongoing debate on whether postmodernist as a cultural movement is able to work as a tool for critique in capitalist societies. I will take Mao II (1991) as a representative example of the narrative pattern of a writer’s resistance to the established order, a stance that is continuous throughout DeLillo’s work. I will argue that the articulation of an artistic ethics within his novels replicates his often quoted statement that “the writer is the person who stands outside society, independent of affiliation and independent of influence.” Moreover, I will claim that the insistence with which this artistic ethics appears in DeLillo’s work can be related to the growing difficulties to classify it as postmodernist.